Bone Morphogenetic Protein-2 in Development and Bone Homeostasis - Daniel Halloran; Hilary W. Durbano; Anja Nohe (Journal of Developmental Biology, 2020)
Bone morphogenetic proteins (BMPs) are multi-functional growth factors belonging to the Transforming Growth Factor-Beta (TGF-β) superfamily. These proteins are essential to many developmental processes, including cardiogenesis, neurogenesis, and osteogenesis. Specifically, within the BMP family, Bone Morphogenetic Protein-2 (BMP-2) was the first BMP to be characterized and has been well-studied. BMP-2 has important roles during embryonic development, as well as bone remodeling and homeostasis in adulthood. Some of its specific functions include digit formation and activating osteogenic genes, such as Runt-Related Transcription Factor 2 (RUNX2). Because of its diverse functions and osteogenic potential, the Food and Drug Administration (FDA) approved usage of recombinant human BMP-2 (rhBMP-2) during spinal fusion surgery, tibial shaft repair, and maxillary sinus reconstructive surgery. However, shortly after initial injections of rhBMP-2, several adverse complications were reported, and alternative therapeutics have been developed to limit these side-effects. As the clinical application of BMP-2 is largely implicated in bone, we focus primarily on its role in bone. However, we also describe briefly the role of BMP-2 in development. We then focus on the structure of BMP-2, its activation and regulation signaling pathways, BMP-2 clinical applications, and limitations of using BMP-2 as a therapeutic. Further, this review explores other potential treatments that may be useful in treating bone disorders.